Sistem Full Day School dalam Menguatkan Karakter Peserta Didik Sekolah Dasar - Joko Prih Triyana; Ery Tri Djatmika; Bambang Budi Wiyono (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This research was aimed to describe a full day school system in strengthening the character of students at Kauman 1 Elementary School and SD Muhammadiyah 4. The study used qualitative descriptive. Techniques for introducing data, interviews and documents. The results of the study (1) the idea of developing a full day school system emerged because the parents of participants were working, the curriculum was in accordance with government programs; (2) planning with academic preparation, conditioning the school, developing syllabus and RPP, and integrating character; (3) implementation consisting of collaboration educational staff, establish communication and cooperation with parents, harmonious relationships between teachers and students, integrate values in learning, self-development, and school culture; (4) student success; (5) the meaning of the school consists of results, implications, supporting factors, inhibitors and efforts. The impact on parents who are helped and the results of the character of the students, namely religious, disciplined, responsible, independent, caring for the environment and caring for socially achieve positive results. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan sistem full day school dalam menguatkan karakter peserta didik di SDN Kauman 1 dan SD Muhammadiyah 4. Penelitian menggunakan deskriptif kualitatif. Teknik pengumpulan data berupa observasi, wawancara, dan dokumen. Hasil penelitian (1) ide pengembangan sistem full day school muncul karena orangtua peserta didik bekerja, kurikulum sesuai dengan program pemerintah (2) perencanaan dengan menyusun kalender akademik, mengondisikan sekolah, mengembangkan silabus dan RPP, dan pengintegrasian karakter (3) pelaksanaan terdiri atas kerjasama tenaga kependidikan, hubungan pendidik dengan orangtua peserta didik, mengintegrasi karakter dalam proses pembelajaran, hubungan baik antara guru dengan peserta didik, program pengembangan diri, serta budaya sekolah, (4) evaluasi terdiri dari penilaian tenaga pendidik, kerjasama dengan orangtua, dan penilaian keberhasilan peserta didik, dan (5) dampak bagi sekolah terdiri dari hasil, implikasi, faktor pendukung, penghambat dan upaya. Dampak bagi orangtua merasa terbantu dan hasil karakter peserta didik yaitu religius, disiplin, tanggung jawab, mandiri, peduli lingkungan, dan peduli sosial mencapai hasil yang positif.